Enhancing Multi-Label Classification via Dynamic Label-Order Learning - Li, Jiangnan; Zhang, Yice; Chen, Shiwei; Xu, Ruifeng (Proceedings of the AAAI Conference on Artificial Intelligence, 2024)
Generative methods tackle Multi-Label Classification (MLC) by autoregressively generating label sequences. These methods excel at modeling label correlations and have achieved outstanding performance. However, a key challenge is determining the order of labels, as empirical findings indicate the significant impact of different orders on model learning and inference. Previous works adopt static label-ordering methods, assigning a unified label order for all samples based on label frequencies or co-occurrences. Nonetheless, such static methods neglect the unique semantics of each sample. More critically, these methods can cause the model to rigidly memorize training order, resulting in missing labels during inference. In light of these limitations, this paper proposes a dynamic label-order learning approach that adaptively learns a label order for each sample. Specifically, our approach adopts a difficulty-prioritized principle and iteratively constructs the label sequence based on the sample s semantics. To reduce the additional cost incurred by label-order learning, we use the same SEQ2SEQ model for label-order learning and MLC learning and introduce a unified loss function for joint optimization. Extensive experiments on public datasets reveal that our approach greatly outperforms previous methods. We will release our code at https: //github.com/KagamiBaka/DLOL.